ASSESSING CREDIT RISK MANAGEMENT PRACTICE IN PRIVATE BANKING IN IRAQ (AN EMPRICAL STUDY IN PRIVATE BANKING IN IRAQ) - H. M. S. MAMANDI, GHAZI (Digital Repository of Theses - SSBM Geneva, 2021)
The study examines the practice of credit risk management in private banks in Iraq. The study compares the practice of credit risk management with the principles of credit risk management issued by Basel Committee on Banking Supervision (2000) and examines how these principles are effectively practiced and implemented. The author collected data by distributing 260 questionnaires to high level bank employees involved in credit risk management. The target population consists of credit staff, credit risk managers, CEO and board members. The study uses Statistical Package for the Social Sciences (SSPS) software program version 26 to analyse the data collected. The results of the data examined are descriptive statistics which include percentages, frequencies such as mean, standard deviation and variance. The study examines regression analysis, ANOVA analysis and Pearson correlation between variables. The study finds the answers to the research questions and test hypotheses and concludes with the description of its findings. Private banks in Iraq can benefit from the findings and suggestions to improve their credit risk management. The author provides recommendations for further studies and identifies some limitations of the study.